Scalar QED as a toy model for higher-order effects in classical gravitational scattering - Zvi Bern; Juan Pablo Gatica; Enrico Herrmann; Andres Luna; Mao Zeng (Journal of High Energy Physics, 2022)
Abstract Quantum Electrodynamics (QED) serves as a useful toy model for classical observables in gravitational two-body systems with reduced complexity due to the linearity of QED. We investigate scattering observables in scalar QED at the sixth order in the charges (two-loop order) in a classical regime analogous to the post-Minkowskian expansion in General Relativity. We employ modern scattering amplitude tools and extract classical observables by both eikonal methods and the formalism of Kosower, Maybee, and O’Connell (KMOC). In addition, we provide a simplified approach to extracting the radial action beyond the conservative sector.